Spatial Variation of Respiratory Diseases in Najaf Governorate in 2016 (Journal of the College of Education for Women, 2019)
The relationship between respiratory diseases and natural geographical variables relative to temperature, relative humidity, wind and solar radiation is a strong one.The environmental factors have impact on increasing the proportion of people with respiratory diseases in the province of Najaf, especially industrial pollution and working conditions as well as the economic level.Ah-Mishkhab was in the first rank in terms of the number of people infected with respiratory diseases reached 135177 and 41%, followed by Najaf governorate which reached its numbers to 77801 and 23%. The district of Kufa ranked third with 42051 and 13%, and the other administrative units at fourth and fifth rank respectively.When comparing diseases and recording cases of each disease, it is noted that bronchitis was the first to be followed by chronic bronchitis, acute tonsillitis, pharyngitis and pneumonia.The difference in the causes that led to respiratory diseases in Najaf governorate between the biological, food, and physical causes.